2018
DOI: 10.1093/hmg/ddy347
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analysis identifiesBARX1andEML4-MTA3as new loci associated with infantile hypertrophic pyloric stenosis

Abstract: Infantile hypertrophic pyloric stenosis (IHPS) is a disorder of young infants with a population incidence of ∼2/1000 live births, caused by hypertrophy of the pyloric sphincter smooth muscle. Reported genetic loci associated with IHPS explain only a minor proportion of IHPS risk. To identify new risk loci, we carried out a genome-wide meta-analysis on 1395 surgery-confirmed cases and 4438 controls, with replication in a set of 2427 cases and 2524 controls. We identified and replicated six independent genomic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 61 publications
0
29
3
Order By: Relevance
“…The seven Table 4, Methods). Genetic variation known to affect levels of our sentinel IHPS significant metabolite PC(38:4) in blood of adults 27 was not associated in our neonatal cohort, nor was associated with IHPS in our previous GWAS meta-analysis 6 . This suggests non-causality of the genetically determined levels of the metabolite PC(38:4) with IHPS, requiring another explanation for the observed association between PC(38:4) levels and IHPS.…”
Section: Targeted Metabolomics and Ihps Associationcontrasting
confidence: 59%
See 1 more Smart Citation
“…The seven Table 4, Methods). Genetic variation known to affect levels of our sentinel IHPS significant metabolite PC(38:4) in blood of adults 27 was not associated in our neonatal cohort, nor was associated with IHPS in our previous GWAS meta-analysis 6 . This suggests non-causality of the genetically determined levels of the metabolite PC(38:4) with IHPS, requiring another explanation for the observed association between PC(38:4) levels and IHPS.…”
Section: Targeted Metabolomics and Ihps Associationcontrasting
confidence: 59%
“…Assessing the effect of FADS1 genetic variant rs174547 [25][26][27] on IHPS was done doing a lookup in our previous genome-wide meta-analysis of IHPS 6 . The association of rs174547 with metabolite levels in our cohort was determined in a linear model adjusted for IHPS status, sex, year of birth (as factor), parity, and gestational age (in weeks).…”
Section: Genetic Variants Associated With Metabolite Levelsmentioning
confidence: 99%
“…The incidence of pyloric stenosis varies between two and five per 1,000 live births and there is a four-to five-fold higher risk in males than females (Peters, Oomen, Bakx, & Benninga, 2014). Three GWAS have been conducted using surgery-confirmed cases and controls from Denmark in the discovery phase (Fadista et al, 2019;Feenstra et al, 2012;Feenstra et al, 2013). Replication samples were drawn solely from the same population as the discovery phase in the earliest study (Feenstra et al, 2012) while the 2013 study (Feenstra et al, 2013) also included replication samples from the United States (mostly non-Hispanic white) and Sweden.…”
Section: Pyloric Stenosismentioning
confidence: 99%
“…Replication samples were drawn solely from the same population as the discovery phase in the earliest study (Feenstra et al, ) while the 2013 study (Feenstra et al, ) also included replication samples from the United States (mostly non‐Hispanic white) and Sweden. In the most recent study, Fadista et al ()) conducted a genome‐wide meta‐analysis, combining their previous GWAS cohort with an additional 427 surgery‐confirmed cases and 2,031 controls, all of Danish descent, in their discovery phase. Genome‐wide significant results were replicated in populations of European descent followed by confirmation in a Hispanic population.…”
Section: Gwas Of Selected Birth Defectsmentioning
confidence: 99%
“…Recent genetic association studies have identified sequence variants associated with isolated IHPS in or near the genes APOA1, MBNL1, EML4, BARX1, and NKX2-5. [10][11][12][13][14] NKX2-5 encodes the homeobox transcription factor NKX2-5, which is essential for normal heart formation and development. 15 Since mutations within NKX2-5 are known to be associated with different forms of congenital heart defects (CHDs), 16 we aimed to investigate whether being diagnosed with a CHD also conferred risk of IHPS.…”
Section: Introductionmentioning
confidence: 99%